2017
DOI: 10.1039/c6ta10308a
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of Fe3+/Fe2+ self-doped nanoporous FeVO4 photoanodes for efficient solar water splitting

Abstract: We demonstrated a facile and effective method to fabricate nanoporous FeVO4 photoanodes for efficient solar water splitting. More importantly, the rationally self-doped Fe2+ or Fe3+ on the FeVO4 photoanode could further improve the photoelectrochemical (PEC) performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 28 publications
2
44
0
Order By: Relevance
“…Several groups have reported the fabrication of FeVO 4 thin films using magnetron cosputtering, spray pyrolysis, dropcasting, and sol-gel methods with reported bandgap energy of 2.0-2.1 eV. [21][22][23][24][25][26][27][28][29][30][31] However, the achieved photocurrents are still very low as compared with the theoretical photocurrent based on the bandgap energy. We have previously identified that the main problem causing the low performance of FeVO 4 films is the poor bulk carrier separation.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have reported the fabrication of FeVO 4 thin films using magnetron cosputtering, spray pyrolysis, dropcasting, and sol-gel methods with reported bandgap energy of 2.0-2.1 eV. [21][22][23][24][25][26][27][28][29][30][31] However, the achieved photocurrents are still very low as compared with the theoretical photocurrent based on the bandgap energy. We have previously identified that the main problem causing the low performance of FeVO 4 films is the poor bulk carrier separation.…”
Section: Introductionmentioning
confidence: 99%
“…The photocurrent density of the undoped material is, however, less than 0.1 mA cm -2 at 1.23 V vs. RHE (potential relative to reversible hydrogen electrode). 27 Efforts have been reported to improve the performance (e.g., doping with W, partial reduction of Fe 3+ /Fe 2+ ), 28,30 but the photocurrent enhancement has been marginal. The cause of such a small photocurrent is not clear, because many intrinsic properties, such as the exact band positions, carrier mobility, and carrier lifetime are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, more attention should be paid to improve the photocurrent densities of a photoanode at lower potentials. In addition to WO 3 , α-Fe 2 O 3 , and BiVO 4 photoanodes, other metal oxide photoanodes such as CuWO 4 [216] , Bi 2 WO 6 [217] , TiFe 2 O 5 [218] , Bi 2 Mo 3 O 12 [217] , CuV 2 O 6 [219][220] , Cu 2 V 2 O 7 [219][220] , Cu 3 V 2 O 8 [221] , and FeVO 4 [222][223] have been developed in recent years.…”
Section: Discussionmentioning
confidence: 99%